Impact of Cryotherapy on Sensory, Motor, and Autonomic Neuropathy in Breast Cancer Patients Receiving Paclitaxel: A Randomized, Controlled Trial - Ng, Ding Quan; Tan, Chia Jie; Soh, Boon Chua; Tan, Mabel May Leng; Loh, Soon Yue; Tan, Yam Eng; Ong, Hui Hui; Teng, Peggy Pei Chee; Chan, Jack Junjie; Chay, Wen Yee; Lee, Joycelyn; Lai, Gillianne; et al. (Frontiers in Neurology, 2020)
Introduction: We conducted a randomized controlled trial evaluating the efficacy and tolerability of cryotherapy in preventing chemotherapy-induced peripheral neuropathy (CIPN) in patients with early breast cancer receiving neo/adjuvant weekly paclitaxel. Methods: Patients were recruited from the National Cancer Centre Singapore and randomized (1:1) to receive either cryotherapy or usual care. Cryotherapy was applied as frozen gloves and socks on all extremities from 15 minutes before paclitaxel until 15 minutes post-infusion every cycle. Efficacy was measured by patient-reported outcomes (Patient Neurotoxicity Questionnaire [PNQ] and EORTC QLQ-CIPN20) and electrophysiological assessments. The primary endpoint was PNQ severity at 2 weeks after 12 cycles of weekly paclitaxel. Results: A total of 46 patients were recruited, of which 8 dropped out before paclitaxel treatment, leaving 38 evaluable. There was no significant difference in PNQ severity between cryotherapy and usual care at 2 weeks after paclitaxel treatment (sensory: p= 0.721; motor: p=1.000). A benefit was observed at 3 months post-paclitaxel based on PNQ (sensory: 14.3% vs 41.2%, p=0.078; motor: 0% vs 29.4%, p=0.012) and CIPN20 (sensory: β=-3.6, 95%CI= -10.5 to 3.4, p=0.308; motor: β=-7.3, 95%CI=-14.6 to 0, p=0.051). Additionally, cryotherapy subjects have lower CIPN20 autonomic score (β=-5.84, 95%CI=-11.15 to -0.524, p=0.031) and higher sympathetic skin response hand amplitudes (β=0.544, 95%CI=0.108 to 0.98, p=0.014), suggesting possible autonomic benefits from cryotherapy. Temporary interruption with cryotherapy occurred in 80.9% of the subjects due to cold intolerance. Conclusions: There is insufficient evidence that cryotherapy prevents sensory neuropathy which may be due to the high rates of cryotherapy interruption in this study. The autonomic benefits of cryotherapy should be further investigated with appropriate outcome measures. ClinicalTrials.gov: NCT03429972 (https://clinicaltrials.gov/ct2/show/NCT03429972).